Financial Behavior and Its Association with Impulsive Buying Behavior: An Empirical Analysis on Gen Z and Millenials - Farhana, Adinda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research explores in depth the intricate relationship between financial behavior and impulsive buying behavior among Generation Z and Millennials two cohorts that have grown up in the digital era and are heavily influenced by online platforms. As digital payment systems, e-commerce applications, and social media marketing continue to expand, these generations face increasing exposure to persuasive digital advertising and instant purchasing options. Such exposure often leads to emotionally driven and unplanned purchases, raising concerns about long-term financial well-being. Using a quantitative research design, the study gathered primary data through structured questionnaires distributed to both Gen Z and Millennial respondents. The research examined several dimensions of financial behavior—such as budgeting practices, saving consistency, expense tracking, and long-term financial planning—to determine how these variables influence impulsive buying tendencies. Statistical analysis revealed a significant negative correlation between disciplined financial behavior and impulsive spending: individuals who demonstrate better control over their finances are less likely to make spontaneous purchases. In contrast, participants with weaker financial management skills tend to exhibit higher impulsivity, particularly within digital shopping contexts where convenience and social influence are strong. These findings emphasize the importance of enhancing financial literacy programs that go beyond basic knowledge to include behavioral awareness and emotional regulation in digital consumption. The study provides valuable insights for educators, policymakers, and marketers, highlighting the need to promote responsible financial decision-making and encourage mindful spending among young adults in the fast-evolving digital economy.